Place branding and translocal chronotopes in Finnish municipality slogans - Voutilainen, Eero (Elsevier, 2026)
This article examines the pragmatics of Finnish municipality slogans by focussing on slogans that include a toponym, that is, a place name other than that of the municipality. We approach our data of 51 slogans from the standpoint of translocal chronotopes – imagery of time, place and social life that connects the municipality with another place. We demonstrate that toponyms position the municipalities geographically, culturally, socially, historically, economically, and politically. We also analyse responses that the slogans evoke in public online discourses. We argue that the interpretation of the slogan is affected by the choice of toponym as well as by structural and interdiscursive choices. The findings are discussed from the perspectives of discourse studies, onomastics, and place-branding research.